Energy Commodity Price Response to COVID-19: Impact of Epidemic Status, Government Policy, and Stock Market Volatility - Czech, Katarzyna; Wielechowski, MichaÅ‚ (International Journal of Energy Economics and Policy, 2021)
The outbreak of the COVID-19 pandemic has hit the global financial markets, including energy commodities. The aim of the paper is to examine the reaction of the energy commodity market to the COVID-19 pandemic, particularly the epidemic status, the stringency of the government anti-COVID-19 policy, and the stock market volatility. We use daily data on the S&P GSCI Energy index, the number of new confirmed COVID-19 global cases, the self-developed Global Stringency Index, and the VIX index. The research covers the period from January 2 to September 30, 2020, i.e. the first phase of the COVID-19 pandemic. Based on a structural vector autoregressive model we observe a significant and negative energy commodity market’s reaction to the changes in the stock market volatility. Moreover, the results imply that the increase in the Global Stringency Index leads to the decline in the S&P GSCI Energy index but the reaction is significant only on the third day after the shock. We reveal no significant impact of global epidemic status on energy commodity prices. Keywords: energy commodities, COVID-19 pandemic; stock market volatility; Global Stringency Index; government anti-COVID-19 policy; structural vector autoregressive model JEL Classifications: G01, G12, G15, H12, Q41 DOI: https://doi.org/10.32479/ijeep.11025